1978
DOI: 10.1111/j.1365-2559.1978.tb01697.x
|View full text |Cite
|
Sign up to set email alerts
|

The hyaline cell: a distinctive feature of ‘mixed’ salivary tumours

Abstract: We have identified and described a distinctive type of cell which is characteristic of the "mixed" salivary tumour. This "hyaline cell" or plasmacytoid cell is particularly common and conspicuous in "mixed" tumours of the palate and other sites in the mouth. It occurs also in tumours of the major glands, but with much lesser frequency. The hyaline cell is found in "mixed" salivary-type tumours in other sites, e.g. the skin. It is not present in the other types of salivary tumour, notably adenoid cystic carcino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
1

Year Published

1980
1980
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(34 citation statements)
references
References 8 publications
0
33
1
Order By: Relevance
“…Epithelioid myoepithelial cells in 2 cases revealed copious hyaline cytoplasm ( Fig. 4) and had the appearance of the so-called hyaline cells in salivary gland tumours [20]. The transitions between the spindle and epithelioid myoepithelial cells were usually gradual, and in 3 cases the shape and arrangement of the myoepithelial cells resembled those seen in synovial sarcoma (Fig.…”
Section: Resultsmentioning
confidence: 96%
“…Epithelioid myoepithelial cells in 2 cases revealed copious hyaline cytoplasm ( Fig. 4) and had the appearance of the so-called hyaline cells in salivary gland tumours [20]. The transitions between the spindle and epithelioid myoepithelial cells were usually gradual, and in 3 cases the shape and arrangement of the myoepithelial cells resembled those seen in synovial sarcoma (Fig.…”
Section: Resultsmentioning
confidence: 96%
“…Due to misinterpretation of these filaments as actin microfilaments, they were originally thought to be neoplastic MECs [27,29,42,43,50]. Though the filaments have been proved to be intermediate filaments, plasmacytoid cells are still considered neoplastic MECs because they are members of the non-luminal cells in pleomorphic adenomas [13].…”
Section: Discussionmentioning
confidence: 99%
“…They are oval to polygonal cells with an eccentrically placed nucleus and an eosinophilic hyaline cytoplasm. They are also the cellular constituents of pleomorphic adenoma [8,20,29]. Because previous studies have not observed the MEC character in plasmacytoid cells [13,14,21,33,38,40], we decided to seek the non-MEC character in these cells.…”
Section: Introductionmentioning
confidence: 99%
“…3B; Lam, 1985) and accounting for the varying amounts of myxochondroid or collagenous "stroma". In some pleomorphic adenomas, there will be a relative balance between luminal and modified myoepithelial cells, whereas in others these tumor cells may predominate with more or less differentiation as chondrocytes (Dardick et al, 1983b;Mills and Cooper, 1981 (Lomax-Smith and Azzopardi, 1978;Sciubba and Brannon, 1982) is produced (Fig. 4B).…”
Section: Ultrastructure Of Thementioning
confidence: 99%